Scale of population synchrony confirms macroecological estimates of minimum viable range size - Juan Carvajal‐Quintero; Lise Comte; Xingli Giam; Julian D. Olden; Ulrich Brose; Tibor Erős; Ana Filipa Filipe; Marie‐Josée Fortin; Katie Irving; Claire Jacquet; Stefano Larsen; Albert Ruhi; et al. (Ecology Letters, 2023)
Global ecosystems are facing a deepening biodiversity crisis, necessitating robust approaches to quantifying species extinction risk. The lower limit of the macroecological relationship between species range and body size has long been hypothesized as an estimate of the relationship between the minimum viable range size (MVRS) needed for species persistence and the organismal traits that affect space and resource requirements. Here, we perform the first explicit test of this assumption by confronting the MVRS predicted by the range‐body size relationship with an independent estimate based on the scale of synchrony in abundance among spatially separated populations of riverine fish. We provide clear evidence of a positive relationship between the scale of synchrony and species body size, and strong support for the MVRS set by the lower limit of the range‐body size macroecological relationship. This MVRS may help prioritize first evaluations for unassessed or data‐deficient taxa in global conservation assessments.